Strategi Manajemen Inovasi dalam Meningkatkan Daya Saing UMKM Kuliner di Kecamatan Karangpucung - Yosinta Pangestuti; Bayu Sudrajat (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to analyze the innovation management strategy implemented by culinary Micro, Small, and Medium Enterprises (MSMEs) in Karangpucung District in an effort to increase competitiveness. This study is a type of field research using a qualitative approach with a case study design, data collected through in-depth interviews, observations, and documentation studies on several culinary MSMEs selected purposively. The results of the study indicate that innovation in culinary MSMEs in Karangpucung is dominated by product innovation and marketing innovation, while process and organizational innovation are still limited. The innovation management strategy implemented tends to be informal and ad-hoc, highly dependent on the owner's intuition and response to market feedback. Identification of innovation opportunities mostly comes from consumer demand and observations of local trends, with idea development through small-scale trial and error. Limited capital, knowledge, and access to technology are the main challenges. Nevertheless, these innovations have been proven to contribute to increased sales, product differentiation, and business sustainability, confirming the crucial role of innovation in the competitiveness of MSMEs.